2008
DOI: 10.1007/s10812-008-9083-9
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of β-cyclodextrin with mercury(II) nitrate

Abstract: 546.492+547.458.68The interaction of β-cyclodextrin with mercury(II) nitrate has been studied using UV, IR, and 1 H NMR spectroscopy, elemental analysis, and quantitative chemical analysis. The optimum conditions for complex formation were established. The stability constant of the 1:1 inclusion complex of β-cyclodextrin and nitrate was calculated. The formation of supermolecules of composition C 42 H 70 O 35 ⋅3Hg(NO 3 ) 2 in solution and on a silica surface chemically modified with β-cyclodextrin was shown.In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…1, curve 2) [50,51]. These data are consistent with the 1 H NMR results [52]. For modified ␤-cyclodextrin the protons' signals of toluenesulfonyl group with chemical shifts ı (ppm) were registered: 2.433 (s) assigned to methyl radical of the toluenesulfonyl group, and also the signals at 7.452 (d) and 7.747 (d) attributed to protons of the benzene ring at the positions 3, 5 and 2, 6 respectively ( Fig.…”
Section: Synthesis Of Mono-(6-o-(toluenesulfonyl))-ˇ-cyclodextrinsupporting
confidence: 88%
See 1 more Smart Citation
“…1, curve 2) [50,51]. These data are consistent with the 1 H NMR results [52]. For modified ␤-cyclodextrin the protons' signals of toluenesulfonyl group with chemical shifts ı (ppm) were registered: 2.433 (s) assigned to methyl radical of the toluenesulfonyl group, and also the signals at 7.452 (d) and 7.747 (d) attributed to protons of the benzene ring at the positions 3, 5 and 2, 6 respectively ( Fig.…”
Section: Synthesis Of Mono-(6-o-(toluenesulfonyl))-ˇ-cyclodextrinsupporting
confidence: 88%
“…It was found that inner cavities of ␤-cyclodextrin molecules are occupied by nitrate-ions [52] and therefore they cannot absorb metal cations. Residual surface aminopropyl groups and functional groups of narrow edge of grafted cyclic oligosaccharides molecules are sorption inactive.…”
Section: Sorption Properties Of ˇ-Cyclodextrin-containing Silicasmentioning
confidence: 99%
“…The formation of inclusion complex between b-CD and Hg(II) has been reported earlier. 65 Such a host-guest interaction assists assembly of b-HPCD-AgNPs when Hg is introduced into the system, which is similar to that of the AuNP assembly formed by a b-CD and osmium complex. 66 Such aggregation-enhanced emission phenomenon has been reported previously.…”
Section: Metal Ion Sensing Studymentioning
confidence: 81%
“…5. Predominant forms of mercury(II) in a weakly acidic range are Hg 2+ and Hg(OH) + [42]. The uptake of mercury(II) for adsorbents 1 and 2 is negligible.…”
Section: Adsorption Of Mercury(ii) Onto a Surface Of Hydroxylated Silmentioning
confidence: 99%